By the Honourable Spencer Phips, Esq ; ... A proclamation for proroguing the General Assembly : ... unto Wednesday the twenty-second day of November next ... then to meet at Harvard-College in Cambridge ... Given at Cambridge, the twenty-eighth day of August 1752 . (Printed by John Draper, printer to his honour the lieutenant-governour and Council, 1752)
August 28, 1752 Proclamation of Lieutenant-Governor Spencer Phips regarding the prorogation of the General Assembly, previously scheduled to meet on September 27th, and ordered postponed until November 22nd.